AquaScouts: ePROs Implemented as a Serious Game for Children With Cancer to Support Palliative Care - Hoffmann, Stefan; Schraut, Robert; Kröll, Thomas; Scholz, Wiebke; Belova, Tatiana; Erhardt, Johann; Gollmer, Daniel; Mauck, Christian; Zacharioudakis, Giorgos; Meyerheim, Marcel; Bonotis, Panos; Kakalou, Christine; et al. (Frontiers in Digital Health, 2021)
MyPal is a European initiative focusing on the use of the so-called electronic Patient Reported Outcome (ePRO) paradigm to support palliative care for cancer patients. As part of its approach, MyPal also focuses on pediatric patients, implementing a specific digital health platform including a serious game to facilitate patients symptom reporting. Symptoms and emotional status can also be reported in an unobtrusive fashion, aiming to reduce reporting fatigue and psychological burden. In this paper, we present the game, named AquaScouts and its key design decisions. The focus is laid on the technical design while also emphasizing on respective challenges. More specifically, we provide insights on the participatory design approach applied during the platform’s design and the respective high-level goals defined as beacons during the design and development process. Furthermore, we present the implementation of the platform, emphasizing on the serious game per se. In addition, the validation process is also presented which was applied before operating the platform under real-world conditions with patients in the clinical context. Finally, we discuss a number of challenges and the prospects of deploying eHealth interventions to support palliative care.